Head in the clouds: a new dwarf frog species of the Physalaemus signifer clade (Leptodactylidae, Leiuperinae) from the top of the Brazilian Atlantic Forest - Leal, Fernando; Zornosa-Torres, Camila; Augusto-Alves, Guilherme; Dena, Simone; Pezzuti, Tiago Leite; Leite, Felipe; Lourenço, Luciana Bolsoni; Garcia, Paulo; Toledo, Luís Felipe (European Journal of Taxonomy, 2021)
In an elevational gradient, the mountain top generally presents a reduced species diversity. However, it is there where we often find microendemic and quite often still undescribed species. That prediction is very common in underexplored Neotropical mountains, like those of the Caparaó National Park – a protected area that includes the highest peak of the Atlantic Forest, a megadiverse domain. Up in its top, we found a dwarf frog of the genus Physalaemus (Anura, Leptodactylidae, Leiuperinae), belonging to the P. signifer clade. After an integrative (morphological, bioacoustical, and genetic) analysis, we were able to describe it as a new species and found it to be sister to P. maculiventris. Due to its very restricted distribution at a site with extreme environmental conditions (which includes fires and frosts) and current instability in national environmental policy, we suggest this to be classified as an endangered species. A brief description of its natural history and the description of the species itself will now enable its proper conservation status categorization and the future planning for conservation actions.